PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN DENGAN OCB SEBAGAI VARIABEL MEDIASI - Prahesti, Devi Shinta; Riana, I Gede; Wibawa, I Made Artha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
The purpose of this study is to analyze and explain the mediating role of organizational citizenship behavior on the relationship of transformational leadership on employee performance of cooperatives in Tabanan. The study population were employees of cooperatives in the district of Tabanan with a sample size is 114 respondents in 25 cooperatives. The sampling technique is done by simple random sampling technique. The research instrument used questionnaire and analysis methods using Partial Least Square (PLS) with software SmartPLS 2.0. The results showed (1) transformational leadership has a positive and significant effect on OCB (2) transformational leadership has a positive and significant effect on employee performance (3) OCB has a positive and significant effect on the performance of employees (4) OCB mediate partially and positive and significant relationship between leadership transformasional and employee performance. The implication of this study indicated that transformational leadership was found as a major factor in improving employee performance.. Suggestions for the results are expand the orientation research in wider scope industry and organization to reach more obtain results.
Keywords: Transformational Leadership, OCB, Employee Performance